THE MENTALITY INFLUENCE TO ORGANIZATIONAL CULTURE ADAPTATION IN INTERNATIONAL COMPANY'S CONDITIONS - O. Solntseva (Вестник университета)
The intersection of different national cultures in the conditions of the international company functioning, in particular in the hotel industry, has been considered. Three groups of cultures, taking into account national features of representatives of different countries, have been offered and collated. The arguments, substantiating the need to take into account the differences of each group and adapt the company’s values and organizational culture in General to the traditions and mentality of the representatives of each country, – have been presented. Expediency of application of the multicultural principles of organizational culture, not contradicting any culture of the world, − has been argued. The conclusion has been made, that this сircumstance is one of the features and conditions of the successful existence of international network companies of hotel and tourism business.